Determining Textbook Cost, Formats, and Licensing with Google Books API: A Case Study from an Open Textbook Project. - Costello, Eamon; Bolger, Richard; Soverino, Tiziana; Brown, Mark (Information Technology & Libraries, 2019)
The rising cost of textbooks for students has been highlighted as a major concern in higher education, particularly in the US and Canada. Less has been reported, however, about the costs of textbooks outside of North America, including in Europe. We address this gap in the knowledge through a case study of one Irish higher education institution, focusing on the cost, accessibility, and licensing of textbooks. We report here on an investigation of textbook prices drawing from an official college course catalog containing several thousand books. We detail how we sought to determine metadata of these books including: the formats they are available in, whether they are in the public domain, and the retail prices. We explain how we used methods to automatically determine textbook costs using Google Books API and make our code and dataset publicly available.